(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Since John Paul Lederach coined the term ‘elicitive’ to describe his approach to conflict transformation (Lederach, 1995), Elicitive Conflict Transformation (ECT) seems to have been slowly yet steadily gaining in popularity. Theneologism reflects that the method of conflict transformation is elicited from and by the parties to a conflict and the energies that they bring with them. As Wolfgang Dietrich has posited that elicitive conflict transformation as the logical application of transrational peace philosophy (Dietrich, 2013), elicitive methods have been applied in programs of peace studies in higher education in a number of countries (Austria, Brazil, Cambodia, Colombia, Ethiopia, Georgia, and Iraq (Echavarría, Hamed & Taylor, 2019, p. 14)) as a holistic pedagogical approach. As it is both a young and expanding field, we will ask the question: what is the current state of the art of elicitive approaches in education with regards to peace? We will elucidate the state of the art by expanding on three aspects: facilitator, curriculum, and institution.